Implementasi Edukasi Hidup Bersih dan Sehat untuk Pencegahan Stunting di PAUD Ar-Rizki Gampong Suak Puntong - Maiza, Maiza Duana; Ibrahim; Jihad, Fikri Faidul (Pencerah, 2024)
Stunting is when a childs’ growth is permanently stunted. This condition is usually characterized by shorter heights than children of the same age. The Clean and Healthy Living Behavior (PHBS) approach includes various positive health behaviors such as personal hygiene, environmental sanitation, and healthy eating. Implementing PHBS can start in early childhood schools. Implementation at the PAUD level is very important in stunting prevention efforts. PAUD is the initial phase of children's formal education, where they begin to learn many things, including about health and hygiene. Methods for the implementation of this service activity: (1) preparation and planning; (2) training and education (3) Demonstration and Practice: (4) Reporting and Dissemination. The results of this service are increased knowledge and practice of PHBS through watching educational videos, practicing how to wash hands with soap properly and correctly, and preventing stunting through the introduction of local-based processed foods and group photos. The conclusion is that clean and healthy living education is very important to prevent stunting, especially in educational institutions such as PAUD Ar-Rizki Gampong Suak Puntong. Unhealthy lifestyles often cause stunting, or stunted physical growth, in children.